Second Five -Year Review of Progress for the Years 1956-57 and 1957-58 Government of Mysore - Planning Commission (Planning Commission, 1956)
THE Second Five-Year Plan was inaugurated on 1st April, 1956. Over two years have now passed and it was considered desirable to present a factual review of progress in the various sectors of the Plan. Seven months after the commencement of the Second Five-Year Plan the new Slate of Mysore came into being. The progress of the Plan in the first two years has been conditioned by the difficulties arising out of Stales Reorganisation. general review of the outlay and resources is first given, followed by detailed notes on individual Sectors of Development.
Planning & Development Department Government of Mysore